A new species of the Ololygon catharinae species group (Anura: Hylidae) from the Cerrado biome, State of Goiás, Central Brazil - de Andrade, Sheila Pereira; Santos, Danusy Lopes; Rocha, Cezar Filho; Pombal, José P. Jr.; Vaz-Silva, Wilian (Zootaxa, 2018)
We describe a new species of Ololygon from the Cerrado biome, Central Brazil. The new species is assigned to the Ololygon catharinae species group based in morphological attributes. Ololygon goya sp. nov. in known only from type locality—Sítio d’Abadia municipality, State of Goiás—and associated with riparian environments connected to seasonal dry forest on the banks of the Corrente river, a tributary of the Paranã river basin. The new species is characterized by the combination of the following characters: medium size (24.4–38.8 mm SVL); snout subovoid in dorsal view; canthus rostralis well defined; males with hypertrophied forearms and nuptial pads; inguinal region and hidden surfaces of thigh with irregular dark brown spots on pale yellowish background. We also describe the external morphology and oral morphology of tadpoles, and the advertisement calls of the new species.